Pseudomonas aeruginosa (IntechOpen, 2024)
This edited volume, Pseudomonas aeruginosa - New Perspectives and Applications, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in immunology and microbiology. Chapters address such topics as P. aeruginosa and hospital-acquired infections, the multidrug resistance of P. aeruginosa, the role of P. aeruginosa in bacterial pathogenesis, and more. The book provides a thorough overview of the latest research efforts by international authors and opens new possible research paths for further novel developments in the field.